Plaque Index, Oral Hygiene Habits, and Depressive Symptomatology as Predictors of Clinical Attachment Loss: A Pilot Study - Norma Idalia Rodríguez Franco; José Moral de la Rubia (International Journal of Dentistry)
Background. The effect of depressive symptomatology on periodontitis is not clear in its path of action. Objective. To test a model to predict clinical attachment loss by direct effect of the dental plaque accumulation, which is a direct effect of worse oral hygiene habits and an indirect effect of greater depressive symptomatology. Methods. Three incidental samples were collected: 35 dental patients with periodontitis, 26 mental health patients with depressive symptomatology, and 29 people from the general population. The Beck Depression Inventory-II and the Oral Hygiene Habits Scale were applied. Plaque index and clinical attachment loss were assessed. Path analysis was used to test the model. The parameters were estimated by the maximum-likelihood method. Results. Depressive symptomatology had no direct effect on oral hygiene habits nor an indirect effect (mediated by oral hygiene habits) on the plaque index in any of the 3 samples. Oral hygiene habits had a large-size direct effect on plaque index and a medium-size indirect effect on clinical attachment loss in the general population sample. The plaque index had a direct effect on clinical attachment loss with a large effect size in general population sample and with a medium effect size in dental patients and depressive symptomatology patients. Conclusion. The model shows that dental plaque accumulation has a direct effect on clinical attachment loss in the 3 samples, and oral hygiene habits have an indirect effect on attachment loss mediated by dental plaque accumulation only in the general population sample. However, depressive symptomatology is not a relevant variable.